Az „átlépés” poétikája: Jegyzetek Borbély Szilárd novellisztikájáról - Angyalosi, Gergely (Studia Litteraria, 2016)
The paper is an overdue review on the volume Árnyképrajzoló – körülírások [Draughtsman of Shadow – Circumlocutions – 2008]. Having construed the relations between the title story and its subtitle, the paper comes to the conclusion that one possible interpretation of the term „circumlocutions” refers to the linguistic strategy that is characteristic of nearly all writings of the volume. Szilárd Borbély was widely acknowledged as one of the most important poets at the time of the publishing of the book. However, as a prose writer, he was in an experimental stage. These writings represent this experimental playground. The essay Egy bűntény mellékszálai [The Secondary Threads of a Crime], as well as its counterpart the volume Halotti pompa [The Splendours of Death], which was a milestone in contemporary Hungarian literature, can be regarded as a masterpiece without exaggeration. The key of the literary success is the fact that the narrator treats the tragic fate of his parents, who were victims of a brutal robbery, as a text. Szilárd Borbély applies a tool of his own profession, narratology to this story. He deconstructs – in the Derrida-esque sense - the traditional ways of narration.